Financial Education: Origin, analysis and evolution of scientific contributions using bibliometric techniques in the Web of Science - Lamadrid Bazán, Jorge E.; De la Torre Torres, Oscar V.; Alfaro-Calderón, Gerardo G. (Unidad Editorial UPTC, 2021)
The development of new information technologies, as well as the profile of new generations, have encouraged financial institutions to seek greater inclusion of their products and services in much of the world's population. Due to the above, there is an increase in the interest of having a society with a greater financial culture that allows it to make better decisions in its particular economy. The growing interest in the field of financial education is also observed in the scientific community. This paper focuses on the search for scientific literature related to financial education between the years 1990-2018. Bibliometric techniques and the Web of Science scientific database are used as a source of information. The objective is to analyze the information found, and visualize the evolution of the concept, the number of publications, the structure of citations, the most influential journals, the authors, universities and countries with more activity in this subject. The results show a total of 2134 articles, it is observed that the greatest production goes from 2016 to 2018. The Economic of Education Review has the largest number of publications and citations. The Institution with more research is the National Bureau of Economic Research and finally the United States of America stands out for its important activity in the area. From the emergence of new variables in financial structures, education in this topic will continue to present new routes to be explored by the scientific community at the service of society. JEL codes: G21, G28, G38, L26 Received: 03/07/2020.  Accepted: 21/09/2020.  Published: 01/12/2021.